Neuro cognitive tracking and corrective action: a way forward in academic performance / Norlaila Abdullah, Suria Fadhillah Md Pauzi and Faizah Azam Ahmad - Abdullah, Norlaila; Md Pauzi, Fadhillah; Ahmad, Faizah Azam (Research Management Institute (RMI), 2013)
The problem of a high performance gap among accounting students in the Faculty of Accountancy of the Universiti Teknologi MARA Pahang does exist. The findings indicated that 64% of diploma and 75% bachelor students have a Cumulative Grade Point Average (CGPA) of below 3.00 (the equivalent grade of B); a gap does exist if measured against the university academic quality standard. Few critical factors were identified, such as poor cognitive skills, lecturers’ level of preparations and suitable teaching methods to influence students’ academic performance. A creative and innovative teaching and learning method, Neuro Cognitive Tracking and Corrective Action (NCTCA) computerized system, has been introduced, implemented and tested. The results indicated that the number of students having GPA of below 3.00 was reduced to 34% and 35% for diploma and bachelor students respectively due to improved cognitive skills. Improvements in cognitive skills for diploma students were knowledge (68%), comprehension (71%), and application (68%) or an average performance gap of 31%, while the bachelor students’ cognitive levels were comprehension (74%), application (70%) and analysis (69%), with an average of 29% as compared to the earlier non-NCTCA phase. This study concludes that when student cognitive skill acquisitions are high, this could result in better GPAs and ultimately decreases the performance gap.